2018
DOI: 10.3329/jcamr.v3i2.36166
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Surgery under Local Anaesthesia: Study of 30 Cases

Abstract: Background: Thyroidectomy is usually done under general anaesthesia.Objective: The purpose of the present study was to present our experience and evaluate effectiveness of thyroid surgery under local anaesthesia.Methodology: This is a cross-sectional study carried out in upazila health complex, Boalkhali, Chittagong and 250 bed General Hospital, Chittagong since January 2013 to December 2015. 30 patient underwent thyroidectomy for benign and malignant diseases under local anaesthesia. All patients are adult fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The average duration of surgery in this study was 90 minutes (45 to 135 minutes). This is similar to what was reported by other authors [9] [12] [13] [15] [17]. In a study conducted in Potiskum, Nigeria, the authors reported a mean duration of surgery of 40 minutes [16], much lower than what was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The average duration of surgery in this study was 90 minutes (45 to 135 minutes). This is similar to what was reported by other authors [9] [12] [13] [15] [17]. In a study conducted in Potiskum, Nigeria, the authors reported a mean duration of surgery of 40 minutes [16], much lower than what was observed in this study.…”
Section: Discussionsupporting
confidence: 91%
“…In a study carried out among patients who had thyroidectomy done under LA due to contraindication to GA, Kamran and colleagues reported 81 females and 19 males [12]. Ahmad and colleagues reported a female preponderance (22 females, and 8 males) in a cross sectional study of thyroid surgery under LA [13]. Similar findings of female preponderance among patients that had thyroidectomy under LA were also reported by other authors [14] [15] [16].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Albert Theodor Billroth was the first surgeon to popularize thyroid surgery, which encompassed primarily drainage of the thyroid cysts, although with concerns of post-operative pain and high levels of recurrence [ 7 ]. Subsequently, thyroidectomy was for years conventionally performed under regional local anesthesia (LA) resulting in loss of sensation and pain in a localized part of the body [ 8 10 ] with some series reporting favorable outcomes on over 20,000 patients as of 1990 [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the advancement of general anesthesia (GA) techniques in which a state of unconsciousness is induced with complete absence of pain and reflexes, the number of thyroidectomies performed under GA increased and ultimately, GA became the preferred method under which thyroidectomy is carried out. In the current surgical practice, majority of surgeons prefer to perform thyroidectomy under GA which offers the advantage of pain-free surgery to the patient, thus reducing their anxiety and enabling a more relaxed operating room environment for the surgeon [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%